2022
DOI: 10.5539/ies.v15n1p187
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Education in the Digital Transformation Process in North Cyprus: A Situation Analysis Study

Abstract: While the world was already moving towards a digital future before 2020, the coronavirus pandemic accelerated that significantly in many sectors. This is certainly true with regard to digital transformation in the classroom, which gathered pace almost overnight when schools shutdown and lessons first moved online. At the time, the shift served to highlight how unprepared most of the sector was for digital transformation. At this point, both teacher and student skills and competencies for digital transformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Digital transformation is more than just the utilization of existing technology, but it is a concept that aims to transform teaching and the learning methods. A recent study revealed that the processes involved in digital transformation lead to the creation of a more effective learning environment for the learners (Yildiz, 2022). In Oman HEIs, having a better learning environment increased the Omani students' motivation to learn.…”
Section: Why Is Digital Transformationmentioning
confidence: 99%
“…Digital transformation is more than just the utilization of existing technology, but it is a concept that aims to transform teaching and the learning methods. A recent study revealed that the processes involved in digital transformation lead to the creation of a more effective learning environment for the learners (Yildiz, 2022). In Oman HEIs, having a better learning environment increased the Omani students' motivation to learn.…”
Section: Why Is Digital Transformationmentioning
confidence: 99%
“…La metodología implementada de revisión de la literatura, mostró la existencia de estudios pertenecientes al norte de Chipre todos con la intencionalidad de medir la competencia digital de los docentes/candidatos concluyendo en los resultados que no existe o no son suficientes los docentes con estas habilidades digitales. Se concluye que la rápida transición y adaptación al proceso de transformación digital, especialmente durante el período de pandemia, expuso esta situación que afecta a los docentes, que constituyen los P á g i n a 2441 actores más importantes de la educación digital, se prevé que se necesita más investigación cualitativa o cuantitativa para interpretar y medir las competencias digitales (Yildiz, 2022).…”
Section: Cualitativounclassified
“…The teaching process is one of the most essential responsibilities of the teacher within the educational process, and this was the central axis in the applied process to achieve a high level of understanding and quality among students [4]. The teacher employs modern and effective teaching techniques to reach new, higher-quality standards [5]. Teaching is the most essential method of education dependent on observation, measurement, and assessment.…”
Section: Introductionmentioning
confidence: 99%